2021
DOI: 10.21203/rs.3.rs-607129/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“What Are The Challenges of Treating Mentally Impaired Patients in The Era of a Pandemic?” : Qualitative Exploration Caregivers

Abstract: Introduction: Caregivers provide support for mental disorders in the form of care such as assistance in daily life activities, but during a pandemic it is a challenge in itself. Objective: To explore the caregiver's experience in caring for clients with mental disorders in remote areas during a pandemic. Methods: Using a phenomenological qualitative research design with 25 participants. The sampling technique used was purposive sampling with data collection techniques using in-depth interviews and field notes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In a way that the quantitative approach cannot do, the qualitative approach offers the most explanation possible. 22 The completeness and validity of the analysis were assessed using the Consolidated Criteria for Qualitative Research Reporting (COREQ). 23…”
Section: Methodsmentioning
confidence: 99%
“…In a way that the quantitative approach cannot do, the qualitative approach offers the most explanation possible. 22 The completeness and validity of the analysis were assessed using the Consolidated Criteria for Qualitative Research Reporting (COREQ). 23…”
Section: Methodsmentioning
confidence: 99%
“…Women's cultural views around breastfeeding must be taken into consideration when discussing PMTCT policies, particularly the decision to breastfeed while taking antiretroviral therapy (ART) [27]. One of Malang's most recent studies, a district health office research, found that traditional views regarding HIV in the area are prevalent, and that informal healthcare is heavily relied upon [28].…”
Section: Discussionmentioning
confidence: 99%